Bootcamp Careers 2024 - PSM feat. TalentCorp - Sahimel Azwal, Sulaiman (Pusat Sains Matematik (PSM), 2024)
The Career Bootcamp 2024 program is an initiative for students with the skills and knowledge needed to succeed in today's dynamic job market. This program was carried out on May 31, 2024 as a collaboration between the PSM UMPSA and the UMPSA Career Center.